The Effect Of Food And Beverage Service Quality On Guest Satisfaction At Hotel Savali Padang - Rahma Dina; Lise Asnur (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study aims to analyze the influence of Food and Beverage Service Quality on Guest Satisfaction at Hotel Savali Padang. The background of this research is based on a situation where the quality of F&B service at Hotel Savali Padang has not fully met the expectations of guests visiting Hotel Savali Padang, such as there are still guest complaints related to F&B service, the level of guest satisfaction with F&B service is still varied, and there is an allegation that the quality of F&B service affects guest satisfaction. The method used in this study is quantitative and causal associative as its approach. Data collection used a closed questionnaire given to 100 respondents concerned, namely, guests of Hotel Savali Padang. The analyzed data were processed using a simple linear regression technique made with SPSS version 29. The results of this research prove that service quality is included in the sufficient category with an achievement score of 56.77%, and guest satisfaction is on a poor scale with a TCR of 44.3%. Statistical tests prove that service quality has a positive and significant impact on guest satisfaction, The results of the analysis obtained that improving service quality can encourage guest satisfaction levels. Thus, improwing the quality of F&B service can increase guest satisfaction and encourage guest loyalty, so that guests will return and be loyal when enjoying the services provided by Hotel Savali Padang,